OPTIMIZING THE IMPLEMENTATION OF THE SIPRAJA APPLICATION IN PUBLIC SERVICES IN RANDEGAN VILLAGE, SIDOARJO REGENCY - Adiba, Fara; Rodiyah, Isnaini (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the implementation of the SIPRAJA (People's Service Information System) application in Randegan Village, Sidoarjo Regency, with a focus on improving efficiency and transparency in public services through the lens of Machfud Siddiq's optimization theory, particularly limited resource indicators. Method: The research employed a qualitative descriptive approach, collecting data through interviews, observations, and documentation involving village heads, officials, and community users. Results: Findings indicate that the SIPRAJA application has succeeded in providing easier access to public services and enhancing transparency. However, significant challenges remain, including limited user understanding, inadequate technological infrastructure, and low levels of digital literacy. Addressing these issues requires more intensive user training, strategic budget planning, and continuous evaluation to ensure sustainable effectiveness. Novelty: This study highlights the integration of optimization theory into the evaluation of e-government implementation at the village level, offering practical insights for policymakers to design targeted strategies that enhance the responsiveness of digital public services and align them with community needs.